Development of attitude control system for hybrid airship vehicle - Malek, Azizi; Sedan, Mohd Fazri; Mohd Harithuddin, Ahmad Salahuddin (Science Publishing Corporation, 2018)
This paper documents and presents the development of attitude control system of Hybrid Airship Unmanned Aerial Vehicle (HAU) that should be able to change its attitude condition based on the response processed from the provided input. This is accomplished by data acquisition method that retrieves data from a flight controller and processes it into the control system without looking in deep on the mathematical model of the airship. Besides that, PID controller is used in order to create a good stable response for the hybrid airship. A working hybrid airship prototype was successfully developed and built, which is five meters in length and has four propellers that is symmetrically distanced to each other. A quadcopter attitude control mechanism is adopted into the hybrid airship to allow for good hovering capability and direct pure attitude control. Outdoor flight tests have been conducted to prove its stability in responding to attitude input given to the hybrid airship attitude controller. A data monitoring software is also written to make the data observation on the behaviour of the hybrid airship response to be easier and understandable. Result demonstrates that the hybrid airship does response to pitch, roll and yaw input from the operator, albeit the lack response stability and speed which can be improved in conservative continuation of research on the airship attitude control system.